Tasawuf di Indonesia: Sejarah, Strategi Dakwah, dan Corak Pemikiran Sufi - Nuriatus Shofiah ABB; Shohebul Hajad (STAI Al-Mujtama Pamekasan, 2025)
Sufism is a teaching that can bring us closer to the one who is the most powerful of all nature, namely Allah SWT. And with this teaching, there must be different styles of thinking, not only in Arab countries, this also happens in Indonesia. This is because each Sufi gives rise to a particular sect according to the belifes and postulates of each Sufi. In this writing, the method used is library research by collecting data and then systematically analyzing and describing it. It was found that the spread of Sufism in Indonesia coincided with the entry and development of Islam in Indonesia, whether with the teachings of philosophical or moral sufism.